Analysis of Modal Choice Preference Between Bus and Train in Post COVID-19 Pandemics: A Case of Tasikmalaya-Jakarta Route - Maulana Aransya; Andri Irfan Rifai; Susanty Handayani (Indonesian Journal of Multidisciplinary Science, 2022)
The COVID-19 pandemic has had an impact on transportation. The impact is still felt when COVID-19 subsidies and community activities have begun to return to normal. Public transportation modes Trains had not operated optimally before the pandemic, resulting in most people choosing bus transportation modes. The purpose of this study is to determine the community's behavior in choosing the mode of transportation between trains and buses on the Tasikmalaya - Jakarta travel route. The method used in this study used the state preference method with attributes of travel time, travel costs, and waiting time. Data analysis was carried out from questionnaire data shared with 100 respondents. The survey results were collected, and linear regression analysis and modeling were conducted using a binomial logit model. Linear regression analysis using the SPSS program obtained the results of the transportation mode selection model, namely (KA-BUS) = -0.293 – 0.389 (X1) – 1.944x10-5(X2) – 0.060 (X3) where X1 Travel time variable, X2 travel cost variable and X3 waiting time variable. It can be concluded that the bus mode of transportation, with a proportion of mode selection of 57.12 %, has a greater chance of being chosen by travelers than the mode of rail transportation, which has a proportion of mode selection of 42,875%.